Changes in Skin Perfusion Pressure After Endovascular Treatment for Chronic Limb-Threatening Ischemia. (April 2021) - Ichihashi, Shigeo; Takahara, Mitsuyoshi; Fujimura, Naoki; Shibata, Tsuyoshi; Fujii, Miki; Kato, Taku; Tsubakimoto, Yoshinori; Iwakoshi, Shinichi; Obayashi, Kenji; Kichikawa, Kimihiko
Purpose: To assess skin perfusion pressure (SPP) changes after endovascular treatment (EVT) of patients with chronic limb-threatening ischemia (CLTI) and to explore preoperative factors that affect SPP changes. Materials and Methods: This prospective, multicenter study recruited 147 patients (mean age 74 years; 99 men) with ischemic wounds at 6 vascular centers in Japan between July 2017 and December 2018. Over half of the patients (92, 63%) were diabetic, and 76 (52%) required dialysis. Sixty-four patients (43%) had WIfI (wound, ischemia, foot infection) wound grades of 2 or 3; 59 (40%) had foot infections. SPP was measured before and 1, 2, 7, and 30 days after EVT to establish inline flow to the ischemic foot based on the angiosome concept when feasible. The anterior and posterior tibial arteries and the peroneal artery were revascularized in 66 (45%), 50 (34%), and 30 (21%) patients, respectively. Results: Both the dorsal and plantar SPPs at 1 or 2 days post-EVT were significantly higher than those at baseline (p<0.001), and both SPPs increased further at 1 month compared with those at 1 (p=0.001) or 2 days (p=0.006) post-EVT. SPP increases occurred on the dorsal and plantar surfaces of the foot regardless of the vessel revascularized. The SPP increase at 1 month after EVT was significantly lower in patients with foot infections than that in those without foot infections (p=0.003). Age, sex, diabetes, dialysis, wound severity, and direct revascularization did not affect the pattern of SPP change. Conclusion: The SPP increased continuously up to 1 month after EVT, though the increase was smaller in patients with wound infections. The SPP on the dorsal and plantar surfaces increased, regardless of the vessel revascularized, which could justify indirect revascularization when direct revascularization is technically challenging.